2014
DOI: 10.1371/journal.pntd.0003146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HTLV-1/2 in Pregnant Women Living in the Metropolitan Area of Rio de Janeiro

Abstract: BackgroundHTLV-1/2 infection can cause severe and disabling diseases in children and adults. The aim of the study was to estimate the prevalence of HTLV-1/2 infection in pregnant women living in the metropolitan area of Rio de Janeiro.Methodology/Principal Findings1,204 pregnant women were tested upon hospital admission for delivery in two public hospitals in the cities of Rio de Janeiro and Mesquita, between November, 2012 and April, 2013. The samples were screened by chemiluminescent microparticle immunoassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
5
13
0
4
Order By: Relevance
“… Most of the reports were performed in Brazil, Peru and Jamaica; all of them are considered endemic regions , , . …”
Section: Methodsmentioning
confidence: 99%
“… Most of the reports were performed in Brazil, Peru and Jamaica; all of them are considered endemic regions , , . …”
Section: Methodsmentioning
confidence: 99%
“…Cases of HTLV-1 infection and HTLV-1 associated diseases have been reported in almost all South American countries including Brazil, Colombia, Argentina, Peru, French Guyana, and Chile [3]. Moreover, some areas of South America such as the Northeast region of Brazil and Northwest Argentina are considered endemic for HTLV-1 [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Infection is considered lifelong and most of the infected subjects remain asymptomatic, becoming viral reservoirs and continuing the chain of transmission [5]. The efficiency of HTLV-1 dissemination is related to the route of transmission [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HTLV-1 antibodies seroprevalence among the pregnant females, who attended the antenatal clinic at the University of Nigeria Teaching Hospital was 0.5% (25). A study performed in Rio de Janeiro showed the prevalence among pregnant females was equivalent to 0.66% (26). A Japanese study reported that the prevalence rate of HTLV-1 among pregnant females was 0.1% (27).…”
Section: Resultsmentioning
confidence: 99%